Macrophage Galactose Lectin Contributes to the Regulation of FVIII (Factor VIII) Clearance in Mice—Brief Report. Issue 4 (2nd February 2023) - Ward, Soracha E.; Guest, Thomas; Byrne, Ciara; Lopes, Patricia; O'Sullivan, Jamie M.; Doherty, Dearbhla; O'Connell, David; Gutierrez Llaneza, Sara; Chion, Alain; Fazavana, Judicael; Fallon, Padraic G.; Preston, Roger J.S.; et al.
Abstract : Background: Although most plasma FVIII (Factor VIII) circulates in complex with VWF (von Willebrand factor), a minority (3%–5%) circulates as free-FVIII, which is rapidly cleared. Consequently, 20% of total FVIII may be cleared as free-FVIII. Critically, the mechanisms of free-FVIII clearance remain poorly understood. However, recent studies have implicated the MGL (macrophage galactose lectin) in modulating VWF clearance. Methods: Since VWF and FVIII share similar glycosylation, we investigated the role of MGL in FVIII clearance. FVIII binding to MGL was assessed in immunosorbent and cell-based assays. In vivo, FVIII clearance was assessed in MGL1 −/− and VWF −/− /FVIII −/− mice. Results: In vitro–binding studies identified MGL as a novel macrophage receptor that binds free-FVIII in a glycan-dependent manner. MGL1 −/− and MGL1 −/− mice who received an anti-MGL1/2 blocking antibody both showed significantly increased endogenous FVIII activity compared with wild-type mice ( P =0.036 and P <0.0001, respectively). MGL inhibition also prolonged the half-life of infused FVIII in FVIII −/− mice. To assess whether MGL plays a role in the clearance of free FVIII in a VWF-independent manner, in vivo clearance experiments were repeated in dual VWF −/− /FVIII −/− mice. Importantly, the rapid clearance of free FVIII in VWF −/− /FVIII −/− mice was significantly ( P =0.012) prolonged in the presence of anti-MGL1/2 antibodies. Finally, endogenous plasma FVIII levels in VWF −/− mice were significantly increased following MGL inhibition ( P =0.016). Conclusions: Cumulatively, these findings demonstrate that MGL plays an important role in regulating macrophage-mediated clearance of both VWF-bound FVIII and free-FVIII in vivo. We propose that this novel FVIII clearance pathway may be of particular clinical importance in patients with type 2N or type 3 Von Willebrand disease.